Tantangan Hukum dalam Pemajakan Penghasilan Digital di Industri Kreatif - Dr. RR. Ella Evrita Hestiandari, S.E, M.M, Dr. RR. Ella Evrita Hestiandari, S.E, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
The taxation of digital income in the creative industry is becoming an increasingly complex issue in today's digital economy era. This study aims to analyse the legal challenges faced in taxing income earned throughdigital media by creative industry players, focusing on cross-jurisdictional issues and the digital economy. The research methodology uses a qualitative approach with primary data collection through interviews with creative industry players and tax law experts, as well as secondary data from relevant literature. The results identified various challenges, including the complexity of digital income classification, crossjurisdictional issues, the influence of different tax policies between countries, and challenges inimplementing the Permanent Establishment (PE) concept in the digital economy. Case studies from different countries provide a concrete picture of the problems faced and the efforts made by countries to address those challenges. Policy recommendations are also prepared to improve tax compliance and support the development of creative industries in the digital era. It is hoped that this research can make a significant contribution in the understanding and resolution of this complex problem in the future.